The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/aac.49.8.3302-3310.2005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antibacterial Activity of Novel Synthetic Cyclic Peptides

Abstract: Cyclic peptides with an even number of alternating D,L-␣-amino acid residues are known to self-assemble into organic nanotubes. Such peptides previously have been shown to be stable upon protease treatment, membrane active, and bactericidal and to exert antimicrobial activity against Staphylococcus aureus and other gram-positive bacteria. The present report describes the in vitro and in vivo pharmacology of selected members of this cyclic peptide family. The intravenous (i.v.) efficacy of six compounds with MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 40 publications
5
122
0
2
Order By: Relevance
“…ICR mice were rendered neutropenic by an i.p. injection of 150 and 100 mg/kg of body weight cyclophosphamide on days 0 and 3, respectively, and infection was induced on day 4 (11). The left thighs of mice were injected with E. coli 25922 (approximately 5 ϫ 10 5 CFU/thigh) prepared as described above.…”
Section: Methodsmentioning
confidence: 99%
“…ICR mice were rendered neutropenic by an i.p. injection of 150 and 100 mg/kg of body weight cyclophosphamide on days 0 and 3, respectively, and infection was induced on day 4 (11). The left thighs of mice were injected with E. coli 25922 (approximately 5 ϫ 10 5 CFU/thigh) prepared as described above.…”
Section: Methodsmentioning
confidence: 99%
“…94 In previous studies, cyclic peptide nanotubes were mainly used for antibacterial applications. 45,95,96 With stacking peptide cycles, nanotubes are able to form transmembrane pores to mimic ion channels in membranes. 45,97,98 Mechanistic studies showed that the antibacterial activity is due to the enhancement of the membrane permeability.…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…45,97,98 Mechanistic studies showed that the antibacterial activity is due to the enhancement of the membrane permeability. 96,97 Moreover, these cyclic peptides could also inhibit virus infections by blocking virus entry or endosome escape in mammalian cells. To inhibit methicillin-resistant bacteria, it is significant to choose a specific peptide sequence against bacterial selectively rather than mammalian cells.…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…Beauvericin (1), enniatins (2), bassianolide (3) and PF1022A (4) and its congeners contain residues with alternating D and L configuration, similar to 6-8-member cyclic D,L-a-peptide antibacterial agents. 10,11 Variations in the amino acid or the hydroxycarboxylic acid positions of the monomers lead to the production of various COD congeners in a given COD producer fungus. COD production in fungi has hitherto been only documented in the Hypocreomycetidae and the Xylariomycetidae, two subclasses of the Sordariomycetes.…”
Section: Istvan Molnarmentioning
confidence: 99%